Salt-resistant toughness self-repairing cement paste system for salt-cavern gas storage and preparation method of salt-resistant toughness self-repairing cement paste system
By adding ultrafine active materials, toughening materials and cementing enhancers to the cementing cement slurry system of the salt hole gas storage, cementing slurry with salt resistance, elasticity and self-healing ability, the cement slurry has been prepared, and the current solution is solved In the art, the lack of performance of cement slurry systems under salt strata geological conditions has significantly improved the cementing quality and wellbore integrity.
Patent Information
- Application Number
- CN202411166642.9
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-08-23
- Publication Date
- 2025-02-11
AI Technical Summary
In the prior art, the cementing cement slurry system of the salt hole gas storage storage is insufficient in salt resistance, elastic toughness, micro-expansion, strong cementing and self-repair capabilities, making it difficult to meet the needs of salt rock strata geological conditions and multi-cycle alternating conditions.
Adopt a salt-resistant toughness self-repair cement slurry system, which consists of G-grade cement, ultra-fine active materials, toughening materials, cementing enhancers, anti-salt water loss agent, low-temperature early strength agent, high-efficiency dispersant, defoaming The agent and the expansion agent are composed of a specific ratio and stirring method.
This cement slurry system has good salt resistance, elasticity, micro-expansion, strong cementing and self-repair capabilities, which can effectively improve the cementing quality of the salt hole gas storage and ensure the integrity of the wellbore. It is suitable for frequent and strong injection and production cycles Gas storage.
Abstract
Description
Technical Field
[0001] The present invention relates to the technical field of salt cavern gas storage drilling, and in particular to a salt-resistant, tough, self-repairing cement slurry system for salt cavern gas storage and a preparation method thereof. Background Art
[0003] Salt cavern gas storage has the advantages of strong peak-shaving capacity and flexibility, and its construction scale has gradually increased in recent years. The construction of salt cavern gas storage requires drilling into the salt layer, and the dissolution of the salt layer during cementing seriously affects the cementing quality; the injection and production rounds of salt cavern gas storage far exceed those of gas reservoir-type gas storage, and the sealing integrity of the cement ring under multiple rounds of strong injection and production alternating stress faces huge challenges, which puts forward strict requirements on the performance of cement slurry for cementing.
[0004] In actual operations, the long salt rock formation needs to be drilled and sealed during the drilling construction of the salt cavern gas storage. Combined with the current situation of conventional well drilling in the salt cavern gas storage, due to the difference in the upper and lower pressure systems of the salt rock layer, and the geological characteristics of the formation lithology, such as heterogeneity, plastic creep, and collapse of salt-bearing mudstone, in addition, due to the low pressure bearing capacity of the formation in some gas storage construction areas, large wellbore size, and weak reference of neighboring well data, and the complex geological conditions, cementing is difficult, and the cementing quality requirements are high. The special geological conditions have caused great difficulties for cementing. At the same time, due to the fact that the wellbore casing and cementing cement ring are prone to wellbore integrity failure, annular gas blowby and pressure under the alternating load of strong injection and strong production in the later stage, it brings huge hidden dangers to the long-term safe operation of the gas storage.
[0005] Salt cavern gas storage wells often encounter extremely thick salt rock layers, and the quality of the wellbore and cementing is difficult to guarantee. The wellbore casing and cement ring are prone to wellbore integrity failure, annular gas blowby and pressure under the action of alternating loads of multiple cycles of strong injection and strong production in the later stage, posing a major safety hazard to the long-term operation of the gas storage. The injection and production wells in gas storage facilities that have been put into production have the following problems in terms of cementing quality: there is annular pressure in the injection and production wells of gas storage facilities. After 1 to 2 years of operation, high pressure will be generated in the casing annulus or between the casing and the oil pipe, and it can be detected that the main component is natural gas; large wellbores, leaky layers, low reservoir pressure and high cementing requirements of gas storage facilities pose challenges to cementing technology and cement slurry systems. Cementing of production casing and the technical casing above it is the main difficulty faced by various gas storage facilities in drilling and completion. There is a lack of unified standards and basis for the optimization of elastic micro-expansion cement slurry systems and the evaluation of gas storage cementing quality; the dissolution of salt rock layers will affect the performance of cement slurry, prolong the thickening time of cement slurry, affect the strength development of cement stone, and fail to prevent the creep of salt rock layers, thereby causing damage to the integrity of the wellbore.
[0006] Therefore, in order to improve the cementing quality of salt cavern gas storage and meet the sealing integrity of cement ring under intensive injection and production, it is necessary to develop a cementing slurry system that is more suitable for the geological conditions of salt rock layers and multi-cycle alternating working conditions of salt cavern gas storage.
[0007] The cement slurry currently used mainly adds a certain concentration of salt water and coagulants to improve the low-temperature early strength performance and salt resistance; elastic agents, fibers and other additives are added to the slurry to improve the brittleness of the cement slurry, and the cement stone performance meets the strength and the influence of subsequent alternating stress. However, when meeting the requirements of salt resistance and elastic toughness, the interface bonding performance between the cement sheath and the salt layer is poor, and the cement stone does not have the ability to self-repair after damage. It is difficult to ensure the cementing quality of the salt layer section and cap layer section, which are important for the integrity of the wellbore during the operation of the gas storage reservoir. Summary of the invention
[0008] The technical problem to be solved by the present invention is to provide a salt-resistant, tough, self-repairing cement slurry system and a preparation method for salt cavern gas storage, so as to solve the problems of poor salt resistance, poor elasticity and toughness, poor micro-expansion, poor strong bonding, and poor self-repairing ability of the cement slurry system in the prior art.
[0009] The technical solution of the present invention to solve the above technical problems is as follows:
[0010] The invention provides a salt-resistant and tough self-repairing cement slurry system for a salt cavern gas storage. The components of the cement slurry system and the mass fractions of each component are: 65-90 parts of G-grade cement, 10-35 parts of ultrafine active materials, 4-10 parts of toughening materials, 3-10 parts of cementing enhancers, 1-5 parts of salt-resistant fluid loss reducers, 0.5-3 parts of low-temperature early strength agents, 0.1-0.5 parts of high-efficiency dispersants, 0.2-1 parts of defoaming agents; 0.5-5 parts of expansion agents, and 40-48 parts of semi-saturated NaCl aqueous solutions.
[0011] Based on the above technical solution, the present invention can also be improved as follows.
[0012] Furthermore, the components of the cement slurry system and the mass proportions of each component are: 85 parts of G-grade cement, 15 parts of ultrafine active materials, 8 parts of toughening materials, 6 parts of cementing enhancers, 3 parts of salt-resistant fluid loss reducers, 1 part of low-temperature early strength agent, 0.25 parts of high-efficiency dispersants, 0.25 parts of defoaming agents; 3 parts of expansion agents, and 47.2 parts of NaCl solutions.
[0013] Furthermore, the ultrafine active material is ultrafine cement, the toughening material is a low elastic modulus self-repairing material, the cementing enhancer is a self-healing emulsion, and the expansion agent is magnesium oxide.
[0014] Furthermore, the particle size of the ultrafine cement ranges from 1 μm to 15 μm.
[0015] Furthermore, the low elastic modulus self-repairing material is a modified rubber, the particle size of the modified rubber is 150 μm to 180 μm, the tensile strength at break is 13.0 MPa to 17.0 MPa, and the air intake expansion rate is 65% to 70%.
[0016] Furthermore, the self-healing emulsion is a modified styrene-acrylic emulsion, the average particle size of the modified styrene-acrylic emulsion is 160nm to 200nm, the solid mass percentage in the modified styrene-acrylic emulsion is greater than or equal to 40%, the anti-gas channeling performance coefficient SPN of the modified styrene-acrylic emulsion is less than 3, and the healing rate in the modified styrene-acrylic emulsion is greater than or equal to 95%.
[0017] Furthermore, in the semi-saturated NaCl aqueous solution, the mass percentage of NaCl is 25% to 27%.
[0018] Furthermore, the cement stone containing the cement slurry system and salt rock-cement slurry has a 24-hour compressive strength of 15MPa-25MPa, a 72-hour compressive strength of 24MPa-37MPa, a salt rock-cement stone interface bonding strength of 1.1MPa-1.8MPa, a linear expansion coefficient of 0.021%-0.043%, and a 7-day elastic modulus of 4.2GPa-5.9GPa.
[0019] The present invention also provides a method for preparing the salt-resistant, tough, self-repairing cement slurry system for salt cavern gas storage as described above, comprising mixing the G-grade oil well cement, the ultrafine active material, the toughening material and the expansion agent to obtain a mixture; mixing the cementing enhancer, the salt-resistant fluid loss agent, the low-temperature early strength agent, the high-efficiency dispersant, the defoaming agent and the semi-saturated NaCl aqueous solution to obtain slurry preparation water; and mixing and stirring the mixture and the slurry preparation water to obtain the cement slurry system.
[0020] Furthermore, a high-speed stirrer is used for the stirring, and the rotation speed of the high-speed stirrer is 3500 to 4500 rpm.
[0021] The beneficial effects of the present invention are:
[0022] (1) The salt-resistant and tough self-repairing cement slurry system for salt cavern gas storage of the present invention has good salt resistance, elastic toughness, micro-expansion, strong bonding, self-repairing and other characteristics;
[0023] (2) The salt-resistant and tough self-repairing cement slurry system for salt cavern gas storage of the present invention, wherein the added ultrafine active material can generate a network flocculation structure product to hinder the dissolution of the salt layer;
[0024] (3) The salt-resistant toughness self-repairing cement slurry system for salt cavern gas storage of the present invention, wherein the added low elastic modulus self-repairing material can improve the mechanical deformation capacity of cement stone, reduce the elastic modulus of cement stone, improve the brittle characteristics of cement stone, and ensure the integrity of cement ring under injection-production alternating stress. At the same time, once the cement ring seal fails, the low elastic modulus self-repairing material in the cement ring can repair microcracks when it expands in the presence of natural gas, so that the cement ring regains its integrity;
[0025] (4) The salt-resistant and tough self-healing cement slurry system for salt cavern gas storage of the present invention, wherein the latex particles in the added self-healing emulsion can fill the pores of the salt rock, improve the interface bonding performance between the cement ring and the salt layer, reduce the water loss of the cement slurry, reduce the permeability of the cement stone, and at the same time, can repair microcracks when encountering natural gas expansion;
[0026] (5) The salt-resistant and tough self-repairing cement slurry system for salt cavern gas storage of the present invention is particularly suitable for salt cavern gas storage, and can effectively improve the cementing quality of salt cavern gas storage and ensure the integrity of the wellbore under frequent and intensive injection and production cycles of salt cavern gas storage;
[0027] (6) The method for preparing the salt-resistant and tough self-repairing cement slurry system for salt cavern gas storage of the present invention has simple steps, mild conditions, and is easy to operate, and can evenly mix the components. DETAILED DESCRIPTION
[0028] The principles and features of the present invention are described below. The examples given are only used to explain the present invention and are not used to limit the scope of the present invention.
[0029] The salt-resistant toughness self-repairing cement slurry system for salt cavern gas storage of the present invention comprises the following components in parts by weight: 65-90 parts of G-grade cement, 10-35 parts of ultrafine active material, 4-10 parts of toughening material, 3-10 parts of cementing enhancer, 1-5 parts of salt-resistant fluid loss reducer, 0.5-3 parts of low-temperature early strength agent, 0.1-0.5 parts of high-efficiency dispersant, 0.2-1 parts of defoamer; 0.5-5 parts of expansion agent, and 40-48 parts of semi-saturated NaCl aqueous solution.
[0030] The salt-resistant and tough self-repairing cement slurry system for salt cavern gas storage of the present invention is prepared with G-class oil well cement as basic material, a certain amount of ultrafine active material, low elastic modulus self-repairing material, cementing enhancer, expander, early strength agent, and a certain proportion of dispersant, salt-resistant fluid loss reducer, defoamer and semi-saturated brine. In addition to having good salt resistance, elasticity and toughness and other properties, it also has the characteristics of micro-expansion, strong cementation, self-repairing and the like, making it particularly suitable for salt cavern gas storage, and can effectively improve the cementing quality of salt cavern gas storage, and ensure the wellbore integrity under frequent and strong injection and production cycles of salt cavern gas storage.
[0031] Preferably, the ultrafine active material is ultrafine cement, the toughening material is a low elastic modulus self-repairing material, and the cementing enhancer is a self-healing emulsion. The specific effects of these components are:
[0032] Ultrafine cement can hydrate quickly to form a network of flocculated products, which hinder the dissolution of salt layers.
[0033] Low elastic modulus self-healing materials can improve the mechanical deformation capacity of cement stone, reduce the elastic modulus of cement stone, improve the brittle characteristics of cement stone, and ensure the integrity of the cement ring under injection-production alternating stress. At the same time, once the cement ring seal fails, the low elastic modulus self-healing materials in the cement ring can expand when exposed to natural gas to repair microcracks and restore the integrity of the cement ring.
[0034] In the self-healing emulsion, latex particles can fill the pores of salt rock, improve the interface bonding performance between the cement sheath and the salt layer, reduce water loss in cement slurry, reduce the permeability of cement stone, and at the same time, expand when encountering natural gas to repair microcracks.
[0035] In addition, low-temperature early strength agent can promote the hydration rate of cement at low temperature and improve the strength of early cement sheath.
[0036] High-efficiency dispersants can depolymerize and disperse the agglomerated cement particles in cement slurry, release free water, improve the fluidity of cement slurry, avoid thixotropy and affect cementing construction.
[0037] The expansion agent is magnesium oxide, which produces large-particle crystals containing crystalline water, which can compensate for the shrinkage of cement during hydration, produce micro-expansion, and further improve the interface bonding strength.
[0038] Preferably, the particle size of the ultrafine cement is in the range of 1 to 15 μm.
[0039] Preferably, the low elastic modulus self-repairing material is modified rubber, the particle size of the modified rubber is 150-180 μm, the tensile strength at break is 13.0-17.0 MPa, and the air intake expansion rate is 65-70%.
[0040] Preferably, the self-healing emulsion is modified with a styrene-acrylic emulsion, the average particle size of the modified styrene-acrylic emulsion is 160-200 nm, the solid mass percentage in the modified styrene-acrylic emulsion is greater than or equal to 40%, the anti-gas channeling performance coefficient SPN of the modified styrene-acrylic emulsion is less than 3, and the healing rate in the modified styrene-acrylic emulsion is greater than or equal to 95%.
[0041] Preferably, the mass percentage of NaCl in the semi-saturated NaCl aqueous solution is 25% to 27%.
[0042] Further preferably, the mass percentage of NaCl is 26.5%.
[0043] Preferably, the cement stone containing the cement slurry system and salt rock-cement slurry has a 24-hour compressive strength of 15 to 25 MPa, a 72-hour compressive strength of 24 to 37 MPa, a salt rock-cement stone interface bonding strength of 1.1 to 1.8 MPa, a linear expansion coefficient of 0.021% to 0.043%, and a 7-day elastic modulus of 4.2 to 5.9 GPa.
[0044] The method for preparing a salt-resistant and tough self-repairing cement slurry system for a salt cavern gas storage reservoir of the present invention comprises the following steps: mixing G-class oil well cement, ultrafine active material, toughening material and expansion agent to obtain a mixture; mixing a cementing enhancer, a salt-resistant fluid loss reducer, a low-temperature early strength agent, a high-efficiency dispersant, a defoaming agent and the NaCl solution to obtain slurry preparation water; and mixing and stirring the mixture and the slurry preparation water to obtain a cement slurry system.
[0045] The preparation method of the present invention prepares the mixture and the slurry water separately and then mixes the two, so that the obtained cement slurry system can be more uniform and the functions of the ultrafine active material, the toughening material and the expansion agent can be well exerted.
[0046] Preferably, the stirring is performed using a high-speed stirrer, and the rotation speed of the high-speed stirrer is 3500-4500 rpm.
[0047] The present invention is illustrated below by means of specific examples.
[0048] Example 1
[0049] The proportions and preparation process of the components in the cement slurry system of this embodiment are as follows:
[0050] 85 parts by weight of G-grade oil well cement, 15 parts by weight of ultrafine active material, 8 parts by weight of toughening material and 3 parts by weight of expansion agent were uniformly mixed to obtain a mixture; 6 parts by weight of cementing enhancer, 3 parts by weight of anti-salt fluid loss agent, 1 part by weight of low-temperature early strength agent, 0.25 parts by weight of high-efficiency dispersant, 0.25 parts by weight of defoamer and 47.2 parts by weight of semi-saturated NaCl aqueous solution were mixed to obtain slurry water; the slurry water and the above mixture were stirred and mixed in a high-speed stirrer at a speed of 4000 rpm to obtain a slurry with a density of 1.93 g / cm 3 The cementing cement slurry system J-1 has a fluidity of 22 cm, a water extraction amount of 16 ml, and an upper and lower density difference of 0. The density, fluidity, water extraction amount, and upper and lower density difference of the obtained cementing cement slurry system are all measured at 25°C and normal pressure.
[0051] The cementing cement slurry system J-1 and the salt rock-cement slurry assembly obtained above were cured at 60° C. for 24 hours, 72 hours and 7 days to obtain cement paste S-1.
[0052] After testing, the 24-hour compressive strength of the cement stone S-1 was 20.8 MPa, the 72-hour compressive strength was 28.6 MPa, the salt rock-cement stone interface bonding strength was 1.6 MPa, the linear expansion rate was 0.042%, and the 7-day elastic modulus was 4.3 GPa.
[0053] Example 2
[0054] The operation process of this embodiment is the same as that of embodiment 1, except that the amount of bonding enhancer added is 10 parts by weight.
[0055] The fluidity of the cementing slurry system J-2 obtained in this example is 20 cm, the amount of water separation is 12 ml, and the upper and lower density difference is 0.
[0056] The cementing cement slurry system J-2 and the salt rock-cement slurry assembly obtained above were cured at 60° C. for 24 hours, 72 hours and 7 days to obtain cement paste S-2.
[0057] After testing, the 24-hour compressive strength of the cement stone S-2 was 18.4 MPa, the 72-hour compressive strength was 27.2 MPa, the salt rock-cement stone interface bonding strength was 1.8 MPa, the linear expansion rate was 0.043%, and the 7-day elastic modulus was 4.2 GPa.
[0058] Example 3
[0059] The operation process of this embodiment is the same as that of embodiment 1, except that the amount of bonding enhancer added is 3 parts by weight.
[0060] The fluidity of the cementing slurry system J-3 obtained in this example is 23 cm, the amount of water separation is 29 ml, and the upper and lower density difference is 0.
[0061] The cementing cement slurry system J-3 and the salt rock-cement slurry assembly obtained above were cured at 60° C. for 24 hours, 72 hours and 7 days to obtain cement paste S-3.
[0062] After testing, the 24-hour compressive strength of the cement stone S-3 was 17.1 MPa, the 72-hour compressive strength was 25.7 MPa, the salt rock-cement stone interface bonding strength was 1.1 MPa, the linear expansion rate was 0.029%, and the 7-day elastic modulus was 5.5 GPa.
[0063] Example 4
[0064] The operation process of this embodiment is the same as that of embodiment 1, except that the amount of toughening material added is 10 parts by weight.
[0065] The fluidity of the cementing slurry system J-4 obtained in this example is 21 cm, the water extraction volume is 33 ml, and the upper and lower density difference is 0.
[0066] The cementing cement slurry system J-4 and the salt rock-cement slurry assembly obtained above were cured at 60° C. for 24 hours, 72 hours and 7 days to obtain cement paste S-4.
[0067] After testing, the 24-hour compressive strength of the cement stone S-4 was 15.3 MPa, the 72-hour compressive strength was 24.6 MPa, the salt rock-cement stone interface bonding strength was 1.1 MPa, the linear expansion rate was 0.032%, and the 7-day elastic modulus was 5.3 GPa.
[0068] Example 5
[0069] The operation process of this embodiment is the same as that of embodiment 1, except that the amount of toughening material added is 3 parts by weight.
[0070] The fluidity of the cementing slurry system J-5 obtained in this example is 23 cm, the amount of water separation is 23 ml, and the upper and lower density difference is 0.
[0071] The cementing cement slurry system J-5 and the salt rock-cement slurry assembly obtained above were cured at 60° C. for 24 hours, 72 hours and 7 days to obtain cement paste S-5.
[0072] After testing, the 24-hour compressive strength of the cement stone S-5 was 23.1 MPa, the 72-hour compressive strength was 34.3 MPa, the salt rock-cement stone interface bonding strength was 1.4 MPa, the linear expansion rate was 0.024%, and the 7-day elastic modulus was 5.9 GPa.
[0073] Example 6
[0074] The operation process of this embodiment is the same as that of embodiment 1, except that the amount of ultrafine active material added is 35 parts by weight.
[0075] The fluidity of the cementing slurry system J-6 obtained in this example is 19 cm, the amount of water separation is 22 ml, and the upper and lower density difference is 0.
[0076] The cementing cement slurry system J-6 and the salt rock-cement slurry assembly obtained above were cured at 60° C. for 24 hours, 72 hours and 7 days to obtain cement paste S-6.
[0077] After testing, the 24-hour compressive strength of the cement stone S-6 was 25.7 MPa, the 72-hour compressive strength was 36.2 MPa, the salt rock-cement stone interface bonding strength was 1.5 MPa, the linear expansion rate was 0.023%, and the 7-day elastic modulus was 5.8 GPa.
[0078] Example 7
[0079] The operation process of this embodiment is the same as that of embodiment 1, except that the amount of ultrafine active material added is 10 parts by weight.
[0080] The fluidity of the cementing slurry system J-7 obtained in this example is 23 cm, the water extraction volume is 30 ml, and the upper and lower density difference is 0.
[0081] The cementing cement slurry system J-7 and the salt rock-cement slurry assembly obtained above were cured at 60° C. for 24 hours, 72 hours and 7 days to obtain cement paste S-7.
[0082] After testing, the 24-hour compressive strength of the cement stone S-7 is 16.2MPa, the 72-hour compressive strength is 27.6MPa, the salt rock-cement stone interface bonding strength is 1.3MPa, the linear expansion rate is 0.029%, and the 7-day elastic modulus is 5.5GPa.
[0083] Example 8
[0084] The operation process of this embodiment is the same as that of embodiment 1, except that the amount of the expansion agent added is 5 parts by weight.
[0085] The fluidity of the cementing slurry system J-8 obtained in this example is 22 cm, the amount of water separation is 28 ml, and the upper and lower density difference is 0.
[0086] The cementing cement slurry system J-8 and the salt rock-cement slurry assembly obtained above were cured at 60° C. for 24 hours, 72 hours and 7 days to obtain cement paste S-8.
[0087] After testing, the 24-hour compressive strength of the cement stone S-8 is 23.2MPa, the 72-hour compressive strength is 34.7MPa, the salt rock-cement stone interface bonding strength is 1.5MPa, the linear expansion rate is 0.037%, and the 7-day elastic modulus is 5.8GPa.
[0088] Example 9
[0089] The operation process of this embodiment is the same as that of embodiment 1, except that the amount of the expansion agent added is 0.5 parts by weight.
[0090] The fluidity of the cementing slurry system J-9 obtained in this example is 22 cm, the water extraction volume is 28 ml, and the upper and lower density difference is 0.
[0091] The cementing cement slurry system J-9 and the salt rock-cement slurry assembly obtained above were cured at 60° C. for 24 hours, 72 hours and 7 days to obtain cement paste S-9.
[0092] After testing, the 24-hour compressive strength of the cement stone S-9 is 19.7MPa, the 72-hour compressive strength is 31.3MPa, the salt rock-cement stone interface bonding strength is 1.2MPa, the linear expansion rate is 0.021%, and the 7-day elastic modulus is 5.5GPa.
[0093] Example 10
[0094] The operation process of this embodiment is the same as that of embodiment 1, except that the amount of the early strength agent added is 3 parts by weight.
[0095] The fluidity of the cementing slurry system J-10 obtained in this example is 22 cm, the amount of water separation is 27 ml, and the upper and lower density difference is 0.
[0096] The cementing cement slurry system J-10 and the salt rock-cement slurry assembly obtained above were cured at 60° C. for 24 hours, 72 hours and 7 days to obtain cement paste S-10.
[0097] After testing, the 24-hour compressive strength of the cement stone S-10 was 26.2MPa, the 72-hour compressive strength was 33.8MPa, the salt rock-cement stone interface bonding strength was 1.3MPa, the linear expansion rate was 0.027%, and the 7-day elastic modulus was 5.6GPa.
[0098] Embodiment 11
[0099] The operation process of this embodiment is the same as that of embodiment 11, except that the amount of the early strength agent added is 0.5 parts by weight.
[0100] The fluidity of the cementing slurry system J-11 obtained in this example is 22 cm, the amount of water separation is 29 ml, and the upper and lower density difference is 0.
[0101] The cementing cement slurry system J-11 and the salt rock-cement slurry assembly obtained above were cured at 60° C. for 24 hours, 72 hours and 7 days to obtain cement paste S-11.
[0102] After testing, the 24-hour compressive strength of the cement stone S-11 was 15.7 MPa, the 72-hour compressive strength was 29.3 MPa, the salt rock-cement stone interface bonding strength was 1.2 MPa, the linear expansion rate was 0.029%, and the 7-day elastic modulus was 5.6 GPa.
[0103] Comparative Example 1
[0104] The proportions and preparation process of each component of this comparative example are as follows:
[0105] 100 parts by weight of G-grade oil well cement, 3 parts by weight of anti-salt fluid loss agent, 41 parts by weight of water, 0.25 parts by weight of defoamer and 47.2 parts by weight of semi-saturated NaCl aqueous solution were mixed to obtain a density of 1.94 g / cm3 The cementing cement slurry system J-12 has a fluidity of 22 cm, a water separation volume of 41 ml, and an upper and lower density difference of 0.
[0106] The cement paste system J-12 and the salt rock-cement paste assembly obtained above were cured at 60° C. for 24 hours, 72 hours and 7 days to obtain cement paste S-12.
[0107] After testing, the 24-hour compressive strength of the cement stone S-12 was 12.4 MPa, the 72-hour compressive strength was 23.9 MPa, the salt rock-cement stone interface bonding strength was 0.7 MPa, the linear expansion rate was -0.004%, and the 7-day elastic modulus was 10.9 GPa.
[0108] Comparative Example 2
[0109] The operation process of this comparative example is the same as that of Example 1, except that no cementing enhancer is added thereto, and the density is 1.93 g / cm 3 The cementing cement slurry system J-12 and the cementing cement slurry system J-13 have a fluidity of 22 cm, a water separation volume of 39 ml, and an upper and lower density difference of 0.
[0110] The cementing cement slurry system J-13 and the salt rock-cement slurry assembly obtained above were cured at 60° C. for 24 hours, 72 hours and 7 days to obtain cement paste S-13.
[0111] After testing, the 24-hour compressive strength of the cement stone S-13 was 19.7 MPa, the 72-hour compressive strength was 28.8 MPa, the salt rock-cement stone interface bonding strength was 0.7 MPa, the linear expansion rate was 0.028%, and the 7-day elastic modulus was 5.6 GPa.
[0112] Comparative Example 3
[0113] The operation process of this comparative example is the same as that of Example 1, except that no toughening material is added thereto, and the density is 1.94 g / cm 3 The cementing cement slurry system J-14 has a fluidity of 24 cm, a water separation volume of 21 ml, and an upper and lower density difference of 0.
[0114] The cementing cement slurry system J-14 and the salt rock-cement slurry assembly obtained above were cured at 60° C. for 24 hours, 72 hours and 7 days to obtain cement paste S-14.
[0115] After testing, the 24-hour compressive strength of the cement stone S-14 was 22.9 MPa, the 72-hour compressive strength was 34.1 MPa, the salt rock-cement stone interface bonding strength was 1.4 MPa, the linear expansion rate was 0.026%, and the 7-day elastic modulus was 10.8 GPa.
[0116] Comparative Example 4
[0117] The operation process of this comparative example is the same as that of Example 1, except that no ultrafine active material is added thereto, and the density is 1.93 g / cm 3 The cementing cement slurry system J-15 has a fluidity of 23 cm, a water separation volume of 32 ml, and an upper and lower density difference of 0.
[0118] The cementing cement slurry system J-15 and the salt rock-cement slurry assembly obtained above were cured at 60° C. for 24 hours, 72 hours and 7 days to obtain cement paste S-15.
[0119] After testing, the 24-hour compressive strength of the cement stone S-15 was 12.4 MPa, the 72-hour compressive strength was 26.5 MPa, the salt rock-cement stone interface bonding strength was 0.6 MPa, the linear expansion rate was 0.028%, and the 7-day elastic modulus was 5.6 GPa.
[0120] Comparative Example 5
[0121] The operation process of this comparative example is the same as that of Example 1, except that no expansion agent is added thereto, and the density is 1.93 g / cm 3 The cementing cement slurry system J-16 has a fluidity of 22 cm, a water separation volume of 28 ml, and an upper and lower density difference of 0.
[0122] The cementing cement slurry system J-16 and the salt rock-cement slurry assembly obtained above were cured at 60° C. for 24 hours, 72 hours and 7 days to obtain cement paste S-16.
[0123] After testing, the 24-hour compressive strength of the cement stone S-16 is 20.5MPa, the 72-hour compressive strength is 31.4MPa, the salt rock-cement stone interface bonding strength is 0.9MPa, the linear expansion rate is -0.003%, and the 7-day elastic modulus is 5.6GPa.
[0124] By comparing the performance test results of the above-mentioned Examples 1 to 11 and Comparative Examples 1 to 5, it is concluded that: compared with the conventional cement paste of Comparative Example 1, the elastic toughness of the cement paste obtained in Examples 1 to 11 is significantly increased, the interface bonding strength with the salt rock is greatly improved, the early compressive strength is increased, and the expansion rate is relatively large; Comparative Example 2 does not add a bonding enhancer, and the interface bonding strength between the obtained cement paste and the salt rock is relatively small; Comparative Example 3 does not add a toughening material, and the obtained cement paste has a high elastic modulus and poor elastic toughness; Comparative Example 4 does not add ultrafine active materials, and the obtained cement paste has a low early strength; Comparative Example 5 does not add an expansion agent, and the obtained cement paste shrinks, which reduces the interface bonding strength to a certain extent.
[0125] By comparing the above embodiments with the comparative examples, it can be analyzed that the system has the advantages of salt resistance, elastic toughness, micro-expansion, high early strength, strong bonding, good rheological properties, etc., is suitable for cementing of salt cavern gas storage, can improve the cementing quality of salt layer sections, and ensure the sealing integrity of cement ring under frequent injection and production.
[0126] In the description of the present invention, it should be noted that the terms "first" and "second" are used for descriptive purposes only and cannot be understood as indicating or implying relative importance or implicitly indicating the number of the indicated technical features. Therefore, the features defined as "first" and "second" may explicitly or implicitly include at least one of the features. In the description of the present invention, the meaning of "plurality" is at least two, such as two, three, etc., unless otherwise clearly and specifically defined.
[0127] In the present invention, unless otherwise clearly specified and limited, a first feature being "above" or "below" a second feature may mean that the first and second features are in direct contact, or the first and second features are in indirect contact through an intermediate medium. Moreover, a first feature being "above", "above" or "above" a second feature may mean that the first feature is directly above or obliquely above the second feature, or simply means that the first feature is higher in level than the second feature. A first feature being "below", "below" or "below" a second feature may mean that the first feature is directly below or obliquely below the second feature, or simply means that the first feature is lower in level than the second feature.
[0128] In the description of this specification, the description with reference to the terms "one embodiment", "some embodiments", "example", "specific example", or "some examples" etc. means that the specific features, structures, materials or characteristics described in conjunction with the embodiment or example are included in at least one embodiment or example of the present invention. In this specification, the schematic representations of the above terms do not necessarily refer to the same embodiment or example. Moreover, the specific features, structures, materials or characteristics described may be combined in any one or more embodiments or examples in a suitable manner. In addition, those skilled in the art may combine and combine the different embodiments or examples described in this specification and the features of the different embodiments or examples, without contradiction.
[0129] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. Any modifications, equivalent substitutions, improvements, etc. made within the spirit and principle of the present invention should be included in the protection scope of the present invention.
Claims
1. A salt-resistant and tough self-repairing cement slurry system for salt cavern gas storage, characterized in that: The components of the cement slurry system and the mass proportions of each component are: 65-90 parts of G-grade cement, 10-35 parts of ultrafine active materials, 4-10 parts of toughening materials, 3-10 parts of cementing enhancers, 1-5 parts of salt-resistant fluid loss reducers, 0.5-3 parts of low-temperature early strength agents, 0.1-0.5 parts of high-efficiency dispersants, 0.2-1 parts of defoaming agents; 0.5-5 parts of expansion agents, and 40-48 parts of semi-saturated NaCl aqueous solutions.
2. The salt-resistant and tough self-repairing cement slurry system for salt cavern gas storage according to claim 1 is characterized in that: The components of the cement slurry system and the mass fraction of each component are: 85 parts of the G-grade cement, 15 parts of the ultrafine active material, 8 parts of the toughening material, 6 parts of the cementitious enhancer, 3 parts of the salt-resistant fluid loss reducer, 1 part of the low-temperature early strength agent, 0.25 parts of the high-efficiency dispersant, 0.25 parts of the defoaming agent, 3 parts of the expansion agent, and 47.2 parts of the NaCl solution.
3. A salt-resistant and tough self-repairing cement slurry system for salt cavern gas storage according to claim 1 or 2, characterized in that: The ultrafine active material is ultrafine cement, the toughening material is a low elastic modulus self-repairing material, the cementing enhancer is a self-healing emulsion, and the expansion agent is magnesium oxide.
4. The salt-resistant and tough self-repairing cement slurry system for salt cavern gas storage according to claim 3 is characterized in that: The particle size of the ultrafine cement ranges from 1 μm to 15 μm.
5. The salt-resistant and tough self-repairing cement slurry system for salt cavern gas storage according to claim 3 is characterized in that: The low elastic modulus self-repairing material is modified rubber, the particle size of the modified rubber is 150 μm to 180 μm, the tensile strength at break is 13.0 MPa to 17.0 MPa, and the air intake expansion rate is 65% to 70%.
6. The salt-resistant and tough self-repairing cement slurry system for salt cavern gas storage according to claim 3 is characterized in that: The self-healing emulsion is a modified styrene-acrylic emulsion, the average particle size of the modified styrene-acrylic emulsion is 160nm-200nm, the solid mass percentage in the modified styrene-acrylic emulsion is greater than or equal to 40%, the anti-gas channeling performance coefficient SPN of the modified styrene-acrylic emulsion is less than 3, and the healing rate of the modified styrene-acrylic emulsion is greater than or equal to 95%.
7. A salt-resistant and tough self-repairing cement slurry system for salt cavern gas storage according to claim 1 or 2, characterized in that: In the semi-saturated NaCl aqueous solution, the mass percentage of NaCl is 25% to 27%.
8. A salt-resistant and tough self-repairing cement slurry system for salt cavern gas storage according to claim 1 or 2, characterized in that: The cement paste containing the cement slurry system and salt rock-cement slurry has a 24-hour compressive strength of 15MPa-25MPa and a 72-hour compressive strength of 24MPa-37MPa; the salt rock-cement paste interface bonding strength in the cement paste is 1.1MPa-1.8MPa, the linear expansion rate is 0.021%-0.043%, and the 7-day elastic modulus is 4.2GPa-5.9GPa.
9. A method for preparing a salt-resistant and tough self-repairing cement slurry system for salt cavern gas storage according to any one of claims 1 to 8, characterized in that: The G-grade oil well cement, the ultrafine active material, the toughening material and the expansion agent are mixed to obtain a mixture; the cementing enhancer, the salt resistance and fluid loss reducer, the low-temperature early strength agent, the high-efficiency dispersant, the defoaming agent and the semi-saturated NaCl aqueous solution are mixed to obtain slurry preparation water; the mixture and the slurry preparation water are mixed and stirred to obtain the cement slurry system.
10. The method for preparing a salt-resistant and tough self-repairing cement slurry system for salt cavern gas storage according to claim 9, characterized in that: The stirring is performed using a high-speed stirrer, and the rotation speed of the high-speed stirrer is 3500-4500 rpm.